Kinetics and mechanism of arsenic sulfides oxidation - Štrbac N.; Mihajlović I.; Minić D.; Živković D.; Živković Ž. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The kinetics of oxidation process of realgar and orpiment natural mineral mixture was studied under non-isothermal conditions. The proposed reaction mechanism and chemical transformation investigated by SEM-EDX, XRD and thermal analysis, are discussed. Using mathematical modeling on results obtained during analysis in non-isothermal conditions, activation energy of this process was determined.